Are Muslims in Turkey Really Green'? - Ugur, Zeynep B. (Worldviews, 2019)
Theoretically, the teachings of Islam can promote environmentally conscious behavior. As the only Muslim majority country to take part in the International Social Science Survey (ISSP), we study indicators of environmental consciousness in Turkey using ISSP 2010. Among all ISSP 2010 participating countries, a cross-country comparison does not provide evidence to support the argument that Islamic religiosity promotes environmental consciousness. In an analysis of individual level data, our overall findings failed to discover a statistically significant relationship between religiosity and environmental consciousness. Yet, this gap between the teachings of Islam and practices of Muslims may be identified as an unexploited potential to foster environmental consciousness in Turkey through a well-articulated religious education that brings together the book of scripture and the book of nature.